Risk Factors for Chronic Stress in Sows Housed in Groups, and Associated Risks of Prenatal Stress in Their Offspring - Lagoda, Martyna Ewa; Marchewka, Joanna; O'Driscoll, Keelin; Boyle, Laura Ann (Frontiers in Veterinary Science, 2022)
Chronic stress has a detrimental effect on sow welfare and productivity, as well as on the welfare and resilience of their piglets, mediated prenatally. Despite this, the specific risk factors for chronic stress in pregnant sows are understudied. Group-housed pregnant sows continuously face numerous challenges associated with aspects of the physical (group type and size, flooring, feeding system) and social (stocking density, mixing strategy) environment. There are many well-known potent stressors for pigs that likely contribute to chronic, physiological stress, including overcrowding, hot temperatures, feed restriction, inability to forage, uncomfortable floors, and poor handling. Some of these stressors also contribute to the development of production diseases such as lameness, which in turn are also likely causes of chronic stress because of the associated pain and difficulty accessing resources. The aim of this review is to discuss potential risk factors for chronic stress in pregnant sows such as space allowance, group size and type (stable/dynamic), feeding level, lameness, pen design, feed system, enrichment and rooting material, floor type, the quality of stockmanship, environmental conditions, and individual sow factors. The mechanisms of action of both chronic and prenatal stress, as well as the effects of the latter on offspring are also discussed. Gaps in existing research and recommendations for future work are outlined.